Synergic Effect of Borneol and Ligustrazine on the Neuroprotection in Global Cerebral Ischemia/Reperfusion Injury: A Region-Specificity Study. (31st July 2016) - Yu, Bin; Ruan, Ming; Zhang, Zhen-Nian; Cheng, Hai-Bo; Shen, Xiang-Chun
Abstract : The cooperation of ligustrazine (LI) and borneol was proved to be much better than each of them in treating cerebral ischemia. However, the mechanism of their synergic therapy is unclear till now. Moreover, whether their cooperation brought different degrees of protection among different brain regions was also unclear. In the present study, the effects of LI, borneol, and their mixture were observed in global cerebral ischemia-reperfusion (GCIR) injury by detecting microcirculation, expressions of caspase-3 and p53, levels of IL-1 β, IL-6, and TNF- α, and contents of SOD, GSH-Px, and MDA in cortex, hippocampus, hypothalamus, and striatum, respectively. Furthermore, Nissl bodies were scored also. Monotherapy of LI or borneol showed obvious improvements in the four regions, specially in cortex and hippocampus. Interestingly, the cooperation of LI and borneol brought some new improvements, specially in hypothalamus and striatum. Thus, the synergic effect of the two drugs showed region-specificity in GCIR injury except the expressions of caspase-3 and p53.